ANALISIS PEMAHAMAN SISWA KELAS VII SMP ADVENT NABIRE TENTANG PERAN NILAI DAN NORMA DALAM SOSIALISASI SEBAGAI UPAYA MEMBENTUK KESADARAN DIRI DAN LINGKUNGAN - Purba, Efa; Muhammad, Azamul Fadhly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the cognitive understanding level of Grade VII students at SMP Advent Nabire regarding values and norms, their interpretation of the role of values in social interaction, and its contribution to the formation of self and environmental awareness. The background of this study is based on the unique challenges in Nabire, Central Papua, where students face complex interactions between religious values, local customs, and global influences through social media. This study uses a sequential exploratory mixed methods approach. Data were collected through cognitive tests, in-depth interviews, and observations of 30 Grade VII students. The results showed that students' cognitive understanding was in the medium category with an average of 68.5. Students tend to be strong in memorizing definitions but weak in case analysis (C4). Interpretatively, students adhere more to customary and family norms than formal school rules, and experience value ambivalence due to social media exposure. In conclusion, students' transactional understanding (fear of sanctions) has not contributed optimally to forming reflective self-awareness and consistent environmental awareness